Broodstock management, reproductive development and larval rearing of the marine ornamental shrimp, Lysmata amboinensis (de Man, 1888) - Omar, Wan Nur Atikah (2019)
Lysmata amboinensis, widely known as "cleaner shrimp," is a favored species in the marine aquarium trade due to its vivid coloration and robust nature. Despite its popularity, attempts to cultivate this species on a large scale have been challenging, primarily due to its extended metamorphosis phase, which can last between 58 and 140 days. This study evaluate the effects of different environmental conditions, specifically salinity and temperature, on major reproductive parameters under controlled laboratory conditions. The study tested the impact of varying salinity levels (30 ppt, 35 ppt, and 40 ppt) on L. amboinensis broodstock. The results indicated that while survival rates remained stable across tested salinity, fecundity and egg volume were significantly affected. Broodstock reared at 30 ppt demonstrated the highest values for fecundity, egg volume, and other reproductive parameters (p < 0.05). For temperature, the broodstock were divided into four groups (22 ºC, 25 ºC, 28 ºC, and 31 ºC). The shrimp showed a wide temperature tolerance range, surviving from 22 ºC to 28 ºC; however, mortality began at 30 ºC, and no shrimp survived beyond 24 hours at 31 ºC. While the broodstock could endure temperatures as low as 22 ºC, they failed to produce fertile eggs. The optimal temperature for reproduction was 25 ºC, yielding nearly twice the fecundity (1420 ± 193) compared to 28 ºC (851 ± 60) and producing eggs with greater size (0.0613 ± 0.0008 mm³) and higher biomass (0.2376 ± 0.0395 g). The effects of different feeds on broodstock reproduction were also assessed, using four diets: squid (Loligo sp.), mussel (Perna viridis), polychaetes (Marphysa moribidii), and a combination of these. The squid diet led to substantial egg loss throughout the incubation period (58.67% ± 3.67%) and lower larval production (97 ± 29) (p < 0.05). Conversely, the mussel diet produced the highest larval count (568 ± 23). The study also explored the life cycle stages of L. amboinensis, identifying seven phases of complete embryonic development over approximately 13 days. Histological analysis showed that the gastrula stage, where organ formation begins, was crucial for embryonic development. Under laboratory conditions, the shrimp achieved ten zoea stages over 55 days, highlighting the lengthy larval development phase. The study further investigated the effect of different diets on larval by feeding larvae six different treatments, including microalgae (Chaetoceros sp., Tetraselmis sp.), a commercial diet, and combinations thereof. Starved larvae and those fed solely with microalgae or the commercial diet showed poor survival rates, with the highest mortality recorded in starved larvae. The combination diet of Tetraselmis sp. and the commercial feed (TSAD) resulted in a 10% higher survival rate (46.67% ± 5.14%) demonstrating its superior performance in supporting larval growth. However, even the TSAD diet was insufficient to promote complete metamorphosis to post-larvae, suggesting that current feeding regimens still require optimization. Research showed that the productivity under captive condition can be enhanced by improving the L. amboinensis broodstock rearing condition and feeding and understanding the biology of the early life of this species.